TRANSLANGUAGING STRATEGIES IN ARABIC LANGUAGE TEACHING AND LEARNING IN UNIVERSITY OF TUN HUSSEIN ONN MALAYSIA - Mohd Ismath, Nurul Hanilah; Abd Aziz, Abdul Hadi (2022)
Nowadays they are many local universities offered foreign languages to be learned and one of them is University of Tun Hussein Onn Malaysia (UTHM). Students may choose one of foreign languages offered in UTHM and they are Japanese, Malay (for non-Malays), Spanish, Mandarin, Arabic and German. Along the learning process they might face difficulties and among the factors are lack of exposure to these languages in the real environment. Therefore, some lecturers need to use cross-language strategies (translanguaging) in learning and teaching process to achieve its objectives. This paper will explain the concept of translaguaging and its implementation in the Arabic class. This study uses a qualitative design, with an observational method. The participants of this study consisted of 29 students of first year consist of different programmes and they are automotive, chemical engineering, and biotechnology at the University of Tun Hussein Onn. The finding of the study show main translanguaging strategy in this learning process, which is support strategy for learning the language. Keywords: Translanguaging Strategies, Arabic Language Teaching and Learning, University of Tun Hussein Onn Malaysia.